1995
DOI: 10.1161/01.hyp.25.6.1260
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Actions of Angiotensin-(1-7) and Angiotensin II in the Brain of Transgenic Hypertensive Rats

Abstract: Lack of specific antagonists to the amino-terminal heptapeptide angiotensin-(1-7) [Ang-(1-7)] prompted us to evaluate the central effects of delivering a specific affinity-purified Ang-(1-7) antibody on the blood pressure and heart rate of 12-week-old conscious homozygous female rats (n = 12) expressing the mouse submandibular Ren-2d gene [(mRen-2d)27] in their genome. Another group of transgenic hypertensive and strain-matched Sprague-Dawley controls were injected with a specific Ang II monoclonal antibody (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 38 publications
2
52
1
Order By: Relevance
“…Similar to the periphery, many of the responses to ANG-(1-7) in the central nervous system oppose those of ANG II. Moriguchi et al (29) showed that intracerebroventricular administration of an ANG II antibody lowered blood pressure in [mRen-2]27 transgenic hypertensive rats; conversely, an antibody that selectively bound ANG-(1-7) raised pressure. In the dorsal medulla oblongata, ANG II attenuated baroreceptor reflex control of heart rate, whereas ANG-(1-7) augmented the reflex, suggesting that the balance of the two peptides sets the sensitivity of the baroreflex.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the periphery, many of the responses to ANG-(1-7) in the central nervous system oppose those of ANG II. Moriguchi et al (29) showed that intracerebroventricular administration of an ANG II antibody lowered blood pressure in [mRen-2]27 transgenic hypertensive rats; conversely, an antibody that selectively bound ANG-(1-7) raised pressure. In the dorsal medulla oblongata, ANG II attenuated baroreceptor reflex control of heart rate, whereas ANG-(1-7) augmented the reflex, suggesting that the balance of the two peptides sets the sensitivity of the baroreflex.…”
Section: Discussionmentioning
confidence: 99%
“…Ang-(1-7) antibody purification and characterization have been described previously. 15 The secondary antibody used was biotinylated goat anti-rabbit for Ang-(1-7) staining or biotinylated horse anti-mouse for ACE2 staining (Vector Laboratories), diluted 1:400 in 1% BSA. Sections were stained brown with 3,3Ј-diaminobenzidine (DAB, Sigma Chemical Co) in Tris-buffered saline (0.05 mol/L, pH 7.6 to 7.7) and counterstained with hematoxylin before being dehydrated and mounted.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…The Ang-(1-7) antibody was purified and characterized by us as described elsewhere. 15 The next day, tissues were washed with PBS and incubated for 3 hours at 4°C with a biotinylated anti-rabbit antibody at a dilution of 1:400 in 1% BSA. Slides were rinsed with PBS, blotted dry, and reacted immunocytochemically by the avidinbiotin method (Vector Laboratories) 16 and stained brown with 3,3Ј-diaminobenzidine (Sigma Chemical Co) in Tris buffered saline (0.05 mol/L, pH 7.6 to 7.7).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%